One-Stage Exchange Arthroplasty for Fistulizing Periprosthetic Joint Infection of the Hip: An Effective Strategy - Marmor, Simon; Kerroumi, Younes; Meyssonnier, Vanina; Lhotellier, Luc; Mouton, Antoine; Graff, Wilfrid; Zeller, Valérie (Frontiers in Medicine, 2020)
Background: Prosthetic hip infection (PHI) is a disastrous scenario after an arthroplasty. International guidelines contraindicate one-stage exchange arthroplasty for fistulizing chronic prosthetic hip infection (FCPHI), nevertheless few surgical teams, mostly from Europe, support one stage procedure for this indication. Questions/Purposes: Analysis of infection recurrence and implant failure of a series of FCPHIs treated with one stage arthroplasty. Patients and Methods: Sixty-six FCPHIs treated with one-stage exchange arthroplasty were prospectively followed up at least 2 years. Clinical, radiological and bacteriological signs suggestive of reinfection were sought, as well as implant failures and PHI related deaths. Results: Thirty-four females and thirty-two males with median age of 69.5 years [61–77] and BMI of 26 kg/m2 [22-31] were included. Fistulae were productive in 50 patients (76%). Staphylococcus was responsible for 45% of PHI and 21% were polymicrobial. Twenty-nine patients (44%) received preoperative antibiotic therapy. After a median 60-month follow-up [35–82], 3 patients (4.5%) presented reinfection (two new infections, one relapse) and 3 patients experienced implant failure (1 femoral fracture, 1 stem breakage, 1 recurrent dislocation). One death was related to PHI. After a minimum of 2 years, the infection control rate was of 95.3% (±0.02). Conclusion: One-stage exchange arthroplasty for FCPHIs showed a good infection control rate similar to that of non-fistulizing PHI. Systematic preoperative microbiological documentation with joint aspiration and, in some specific cases, the use of preoperative antibiotic therapy are among the optimizations accounting for the success of the one-stage arthroplasty. In light of these results, and those of other studies, international recommendations could evolve. Level of Evidence: Descriptive therapeutic prospective cohort study. Level of evidence: IV.